1988
DOI: 10.1007/bf00261966
|View full text |Cite
|
Sign up to set email alerts
|

Urinary biochemical profile of patients with ureteric calculi in Jodhpur region (north western India)

Abstract: Urine chemistry of 42 normal subjects (NS) and 59 ureteric stone formers (SF) from Jodhpur region of Rajasthan, India is presented. Twenty four hour urinary levels of calcium, oxalic acid and uromucoids were significantly higher and levels of magnesium, citric acid and inorganic phosphorus were significantly lower in SF as compared to NS. No significant difference was observed in the uric acid, sodium and potassium levels in the two groups. Significant correlation was observed between calcium and magnesium; ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The high incidence of calcium oxalate stones in our region may be because of its hot climate, oxalate-rich diet, and decreased fluid intake. [ 20 21 ] On subgroup analysis based on the patient's age, we observed that the proportion of calcium oxalate stone was increasing whereas that of uric acid, struvite, and cystine was decreasing with age, and this trend was similar for all whether it was renal, ureteric, or vesical calculus. Gabrielsen et al .…”
Section: Discussionmentioning
confidence: 91%
“…The high incidence of calcium oxalate stones in our region may be because of its hot climate, oxalate-rich diet, and decreased fluid intake. [ 20 21 ] On subgroup analysis based on the patient's age, we observed that the proportion of calcium oxalate stone was increasing whereas that of uric acid, struvite, and cystine was decreasing with age, and this trend was similar for all whether it was renal, ureteric, or vesical calculus. Gabrielsen et al .…”
Section: Discussionmentioning
confidence: 91%
“…This fi nding is also in contrast to Western studies where staghorn stones more often are composed of struvite. The predominance of calcium oxalate stones also has been shown in various other studies [ 15,16 ] . Older studies from the northwestern region of India revealed a higher proportion of struvite stones [ 7,10 ] .…”
Section: Compositionmentioning
confidence: 79%
“…In a study from Rajasthan, though magnesium intake was normal in both normal subjects and stone formers, the mean excretion of magnesium was lower than normal in all the groups, suggesting its defective absorption in this population [ 16 ] . Lower concentration of urinary magnesium was found in stone formers from Chandigarh, suggesting its inhibitory role in urolithiasis [ 46 ] .…”
Section: Magnesiummentioning
confidence: 98%
“…[12] Ureteric stone analysis done in Jodhpur also reported a similar finding. [13] Hypercalciuria and hyperparathyroidism are the risk factors for calcium stone formation. Excessive consumption of Oxalate containing foods or excessive absorption of oxalate in enteric diseases or ileojejunal surgery or Vitamin C supplementation [14] contributes to oxalate stone formation.…”
Section: Discussionmentioning
confidence: 99%